The Effect of Education by Visual Self-assessment on the Operating Room Technician\'s Knowledge, Self-esteem, and Performance in Advanced Cardiopulmonary Resuscitation - Amir Azadi; Sorour Mosleh; Nasrollah Alimohammadi; Zarrin Tansaz; Narges Kheirollahi (Iran University of Medical Sciences, 2021)
Background & Aims: Cardiopulmonary resuscitation is one of the most critical medical emergencies. The effect of trained and skilled people on resuscitation has been positive. This study aimed to investigate the impact of visual self-assessment training on the level of knowledge, self-esteem, and performance of operating room personnel in the field of advanced cardiopulmonary resuscitation.  Materials & Methods: This Semi-experimental pre-test, post-test single-group study was performed with the participation of 32 operating room technicians. The intervention was in the form of a cardiopulmonary resuscitation workshop and takes a video from resuscitation operation on the model by each of the participants and then replays the video for self-assessment. Knowledge, self-esteem questionnaire, and self-assessment performance checklist were given to each participant to complete before, immediately after, and eight weeks after intervention. At the same time, a performance observation checklist was completed for them by the researcher. Data were analyzed by SPSS v. 16 software, and repeated measures analysis, Greenhouse-Geisser and Bonferroni post hoc test, and paired t-test were used. Results: Data analysis was performed on 28 operating room technicians participants in the study. Demographic data of participants showed 89.29% were female, 67.86% had a bachelor's degree in the operating room, and the mean age of participants was 39.37 years. The comparison of the mean scores of operating room technicians' knowledge and self-esteem three times was significant (P<0.001). Also, the comparison of the mean performance self-assessment score and the mean performance score observed immediately after and eight weeks later were significant (P<0.001).  Conclusion: Visual self-assessment method effectively increases the knowledge, self-esteem, and performance of operating room technicians in the field of cardiopulmonary resuscitation. Especially since their self-esteem and performance will be indelible.